Penerapan Asas Keadilan dalam Perjanjian Bagi Hasil Laut (Ikan) Antara Pemilik Kapal dan Anak Buah Kapal di Desa Lamahala Jaya Kecamatan Adonara Timur Kabupaten Flores Timur - Takdir Abdurahman; Siti Ramlah Usman; Helsina Fransiska Pello (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The purpose of this research is to analyze the application of the principle of justice in the agreement of marine profit sharing (fish) between the ship owner and the crew in Lamahala Jaya Village, East Adonara District, East Flores Regency. The type of research used by the author is Empirical Legal research, the type of data used in this research is qualitative data. The data used in the research based on the relevance of the source data, namely primary, secondary and tertiary data. The results of this study suggest that: (1) The application of the principle of justice in the agreement of marine profit sharing (fish) between the ship owner and the crew in Lamahala Jaya Village, East Adonara Subdistrict, East Flores Regency which is carried out has been going well but is still not maximized in the distribution of results, many of the crew feel that the division is not evenly distributed due to the wages received are different. (2) The agreement is made orally (not written) so that it is detrimental to the crew because it does not have legal force in proving this is even more beneficial to the ship owner, the low productivity of the performance of the crew which affects the amount of wages received different from other crew members, increasing operational needs, the wages received by the crew can be low compared to the captain and ship owner.